Poly (Lactic Acid)/D-Limonene/Zno Bio-Nanocomposites with Antimicrobial Properties - Ortiz-Nunez, J; Zapata-Ramirez, P; Canales-Arévalo, D; Loyo-Davila, C; Moreno-Serna, V (John Wiley and Sons Inc, 2022)
Antimicrobial films of poly (lactic acid) (PLA)/D-limonene/zinc oxide (ZnO)-based bio-nanocomposites were prepared via melt compounding and subsequent thermocompression. D-limonene was incorporated at concentrations of 10 or 20 wt%, and ZnO pure nanoparticles and those organically modified with oleic acid (O-ZnO), with an average diameter of 13.5 nm, were included at concentrations of 3, 5, and 8 wt%. The plasticizing effect of D-Limonene was corroborated by a decrease in the glass transition temperature compared to pure PLA. The presence of ZnO and O-ZnO in the PLA matrix promoted a slight increase in the degree of crystallinity due to its nucleant performance. Although ZnO and O-ZnO induced lower thermal stability and slightly decreased microhardness in the composites, excellent antimicrobial performance was demonstrated. Both ZnO and O-ZnO nanocomposites reached 99.9% of effectiveness for nanoparticles content above 5 wt%, regardless of the source of irradiation, D-limonene concentration, and nanoparticle modification. Therefore, these bio-nanocomposites will allow for future advances in sustainable antimicrobial materials for the medical or food packaging fields. © 2021 Wiley Periodicals LLC.